Strategic management in enhancing study program accreditation at higher education institutions - Sulaeman, Sulaeman; Nuhalisa, Nuhalisa (Indonesian Institute for Counseling, Education and Therapy (IICET), 2025)
This study aims to analyze and explore the practices of Strategic Management in improving the accreditation of study programs at the Faculty of Tarbiyah, IAIN Bone. The type of research used in this study is descriptive qualitative research. Data was obtained from the Faculty and Study Program leaders, as well as the Faculty Accreditation Team, to gather information regarding the implementation of Strategic Management in achieving Excellent accreditation for the Study Program. Data were collected through in-depth interviews, observations, and documentation, with the data analysis technique involving collection, reduction, presentation, and drawing conclusions. Based on the research findings, there are three main interconnected pillars in achieving Excellent Accreditation: 1) Quality-oriented strategic planning: Effective planning begins with formulating a vision and mission aligned with the faculty's and university's goals, involving active participation from stakeholders, and supported by a comprehensive SWOT analysis to identify strengths, weaknesses, opportunities, and threats. 2) Collaborative and adaptive implementation: The implementation phase emphasizes the importance of a supportive organizational structure, transformational leadership, and a collaborative and adaptive work culture that involves the entire team in achieving accreditation targets. Team solidarity, effective communication, and the role of quality assurance are key to success in this phase. 3) Sustained strategic evaluation and control: Strategic evaluation and control ensure that every step is on track, allowing for quick improvements and adaptation to changes. Regular evaluation processes, both formal and informal, focus on accreditation indicators and encourage organizational learning. This study shows that an integrated strategic approach, supported by leadership commitment and active participation from all elements, is essential to achieving and maintaining excellent program accreditation amidst the dynamics of higher education.